PERAN KESEKRETARIATAN DALAM MENINGKATKAN EFISIENSI OPERASIONAL DI PERUSAHAAN YANG BERGERAK DI BIDANG TRANSPORTASI KELAUTAN (STUDI KASUS : PERUSAHAAN PT PELNI (PERSERO) CABANG SURABAYA) - Nafalia Dini Faradilla; Yuniningsih (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the contribution of the secretarial department in increasing operational effectiveness in companies engaged in sea transportation, focusing on a case study of PT PELNI (Persero) Surabaya Branch. The issue discussed is how the secretarial role can overcome the problem of competition with other types of transportation and to improve company performance. The method applied in this study is qualitative with a library research approach, which serves to collect and analyze information from various sources, including books, scientific journals, articles, and research reports that are in line. The findings of this study confirm that secretarial functions as a key element in time management, information flow, communication, and coordination arrangements. The implementation of Standard Operating Procedures (SOPs), training in technology, as well as the System of Office Automation (SOK) by the secretarial office has a major impact on the company's operational efficiency. In addition, secretarial plays an important role in conveying critical information to management to assist in strategic decision-making and improving service quality.